Step
*
of Lemma
bag-append-no-repeats
∀[T:Type]. ∀[as,bs:bag(T)].
  uiff(bag-no-repeats(T;as) ∧ bag-no-repeats(T;bs) ∧ (∀z:T. (z ↓∈ as 
⇒ (¬z ↓∈ bs)));bag-no-repeats(T;as + bs))
BY
{ ((UnivCD THENA Auto) THEN D 0 THEN (D 0 THENA Auto)) }
1
1. T : Type
2. as : bag(T)
3. bs : bag(T)
4. bag-no-repeats(T;as) ∧ bag-no-repeats(T;bs) ∧ (∀z:T. (z ↓∈ as 
⇒ (¬z ↓∈ bs)))
⊢ bag-no-repeats(T;as + bs)
2
1. T : Type
2. as : bag(T)
3. bs : bag(T)
4. bag-no-repeats(T;as + bs)
⊢ bag-no-repeats(T;as) ∧ bag-no-repeats(T;bs) ∧ (∀z:T. (z ↓∈ as 
⇒ (¬z ↓∈ bs)))
Latex:
Latex:
\mforall{}[T:Type].  \mforall{}[as,bs:bag(T)].
    uiff(bag-no-repeats(T;as)
    \mwedge{}  bag-no-repeats(T;bs)
    \mwedge{}  (\mforall{}z:T.  (z  \mdownarrow{}\mmember{}  as  {}\mRightarrow{}  (\mneg{}z  \mdownarrow{}\mmember{}  bs)));bag-no-repeats(T;as  +  bs))
By
Latex:
((UnivCD  THENA  Auto)  THEN  D  0  THEN  (D  0  THENA  Auto))
Home
Index